The influence of smoking and impaired glucose homoeostasis on the outcome in patients presenting with an acute coronary syndrome: a cross-sectional study. Issue 7 (3rd July 2014) - Odeberg, Jacob; Freitag, Michael; Forssell, Henrik; Vaara, Ivar; Persson, Marie-Louise; Odeberg, Håkan; Halling, Anders; Råstam, Lennart; Lindblad, Ulf
Abstract : Objectives: Smoking, diabetes, male sex, hypercholesterolaemia and hypertension are well-established risk factors for the development of coronary artery disease (CAD). However, less is known about their role in influencing the outcome in the event of an acute coronary syndrome (ACS). The aim of this study was to determine if these risk factors are associated specifically with acute myocardial infarction (MI) or unstable angina (UA) in patients with suspected ACS. Design: Cross-sectional study. Setting: Patients admitted to the coronary care unit, via the emergency room, at a central county hospital over a 4-year period (1992–1996). Participants: From 5292 patients admitted to the coronary care unit, 908 patients aged 30–74 years were selected, who at discharge had received the diagnosis of either MI (527) or UA (381). A control group consisted of 948 patients aged 30–74 years in whom a diagnosis of ACS was excluded. Main outcome measures: MI or UA. Results: Current smoking (OR 2.42 (1.61 to 3.62)), impaired glucose homoeostasis defined as glycated haemoglobin ≥5.5% + blood glucose ≥7.5 mM (OR 1.78 (1.19 to 2.67)) and male sex (OR 1.71 (1.21 to 2.40)) were significant factors predisposing to MI over UA, in the event of an ACS. Compared with the non-ACS group, impaired glucose homoeostasis, male sex, cholesterol level and age were significantly associated with development of an ACS (MI and UA). Interestingly, smoking was significantly associated with MI (OR 2.00 (1.32 to 3.02)), but not UA. Conclusions: Smoking or impaired glucose homoeostasis is an acquired risk factor for a severe ACS outcome in patients with CAD. Importantly, smoking was not associated with UA, suggesting that it is not a risk factor for all clinical manifestations of CAD, but its influence is important mainly in the acute stages of ACS. Thus, on a diagnosis of CAD, the cessation of smoking and management of glucose homoeostasis are of upmost importance to avoid severe subsequent ACS consequences.